2015
DOI: 10.1007/s13197-015-1782-7
|View full text |Cite
|
Sign up to set email alerts
|

Effect of glycosylation with xylose on the mechanical properties and water solubility of peanut protein films

Abstract: This study aimed at improving the mechanical properties and water solubility of peanut protein isolate (PPI) films by glycosylating with xylose (X). The modification process of glycosylation was optimized by using response surface methodology (RSM). The effects of pH, temperature and time on degrees of glycosylation (DG), tensile strength (TS), elongation (E), solubility and microstructure of xylose glycosylated PPI films (PPI-XF) were determined. The changes of DG in different conditions indicated that crossl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 34 publications
0
11
0
Order By: Relevance
“…Extensive scientific evidence shows that emulsifying, gelling, foaming, rheological and other properties of proteins can be modified efficiently by the protein glycation via the Maillard reaction . Mechanical properties of peanut protein film can be improved by the prior glycation with xylose . In addition, casein hydrolysates after their Maillard reaction with xylose demonstrate enhanced inhibition on angiotensin I converting enzyme …”
Section: Introductionmentioning
confidence: 99%
“…Extensive scientific evidence shows that emulsifying, gelling, foaming, rheological and other properties of proteins can be modified efficiently by the protein glycation via the Maillard reaction . Mechanical properties of peanut protein film can be improved by the prior glycation with xylose . In addition, casein hydrolysates after their Maillard reaction with xylose demonstrate enhanced inhibition on angiotensin I converting enzyme …”
Section: Introductionmentioning
confidence: 99%
“…Modication of peanut proteins by glycosylation or cross-linking with saccharides is a potential way to improve the mechanical strength and the barrier properties of the lms by reinforcing the intermolecular bonds. [6][7][8] In literature, several recent papers deal with the improvement of the mechanical and barrier properties of protein-based lms by glycosylation reactions. 4,9,10 Glycosylation with gum arabic 11 or glucomannan 9 increases the tensile strength, decreases the water vapor permeability of protein lms, but decreases the elongation ability.…”
Section: -4mentioning
confidence: 99%
“…12,13 They also exhibit a more efficient plasticizing effect and lead to a stronger and tighter protein networking with stronger intermolecular covalent bonds. Lin et al 4,7 reported that crosslinking with xylose increases the strength and elongation of peanut protein lms and also decreases quite remarkably their solubility in water. Therefore, xylose could be a good choice for the formation of protein-polysaccharides lms.…”
Section: -4mentioning
confidence: 99%
See 1 more Smart Citation
“…Unsurprisingly, they have excellent hydrophilicity, biocompatibility, and specific recognition properties, which are promising in the application of bio-separation, biomedical engineering, and tissue engineering, etc. [10][11][12][13][14].Previous studies have reported that the carbohydrates can be conjugated onto the surfaces via several methods [15][16][17][18][19][20][21][22][23][24]. Examples include non-covalent immobilization through hydrogen bonding, hydrophobic interaction, van der Waals force, electrostatic interaction, covalent immobilization through different chemical reactions including Michael addition, click and surface-initiated atom transfer radical polymerization.…”
mentioning
confidence: 99%